A healing conversation : how healing happens - Symington, Neville (Karnac, 2006)
This volume, evolving from a series of lectures, attempts to answer the question: why does conversation have the power to heal? Combining his own substantial experience of psychoanalysis with rigorous academic research, respected psychoanalyst and author Neville Symington reminds us that psychoanalysis constitutes 'not just an intellectual effort but an emotional transformation' facilitated through healing conversation.